Neural circuits regulating sexual behaviors via the olfactory system in mice. (March 2019) - Ishii, Kentaro K.; Touhara, Kazushige
Highlights: The repertoire of identified sexual behavior-relevant olfactory cues is expanding. The amygdala plays a role in processing information of the olfactory cues. The dopaminergic system plays a role in regulating appetitive sexual behaviors. The hypothalamus plays a role in controlling consummatory sexual behaviors. Internal states modulate sensorimotor processing during sexual behavior. Abstract: Reproduction is essential for any animal species. Reproductive behaviors, or sexual behaviors, are largely shaped by external sensory cues exchanged during sexual interaction. In many animals, including rodents, olfactory cues play a critical role in regulating sexual behavior. What exactly these olfactory cues are and how they impact animal behavior have been a central question in the field. Over the past few decades, many studies have dedicated to identifying an active compound that elicits sexual behavior from crude olfactory components. The identified substance has served as a tool to dissect the sensory processing mechanisms in the olfactory systems. In addition, recent advances in genetic engineering, and optics and microscopic techniques have greatly expanded our knowledge of the neural mechanisms underlying the control of sexual behavior in mice. This review summarizes our current knowledge about how sexual behaviors are controlled by olfactory cues.